The Implications of factionalism in political parties: the case of ZANU-PF in the post- independence era - Zimbudza, K. (BUSE, 2019)
This study sought to analyse the types, challenges, and benefits of factionalism in the Zimbabwe African National Union, Patriotic Front (ZANU-PF). The study was motivated by the fact that the history of ZANU-PF has been characterised by factionalism in both pre and post-independence periods. The overall objective of this study was to examine factionalism in ZANU-PF and propose options for its management. This study was a case study of factionalism in ZANU-PF. The issue of factionalism, its causes, and management is a highly contested and subjective issue in Zimbabwe and qualitative approach seemed to be more appropriate. The population was made up of officials in ZANU-PF, non governmental organisations, and political analysts. There was use of quota sampling to ensure some representativeness of all the stakeholder groups pertaining to the issue of factionalism in ZANU-PF. Purposive or expert sampling technique was also in use to identify the institutions and individuals believed to be good prospects for required data. The main tools for data collection in this study were interviews. This study had qualitative data, which was analysed using thematic analysis. The research found out that factionalism is about the power dynamics in a political entity. In ZANU-PF, there have been many factions, including cooperative, competitive, and degenerative factionalism. The challenges caused by factionalism in ZANU-PF were the erosion of internal cohesion, challenges in managing the party, negative influence on electoral success, and ineffective decision-making. The main benefit of factionalism was the widening of the democratic) space. The research also found out that leadership plays an important role in managing factions in political parties. The study recommended that members of political parties ought to be tolerant to the emergence of divergent groups within the party. Another recommendation was that there was a need to strengthen rules and regulations against violence and to make sure that divergent view are respected in political parties. It was also recommended that there was a need for a strong and visionary leadership. Having sound disciplinary and grievance handling procedures is essential.
Keywords: Parties factionalism; Post Independence; ZANU-PF